-96-7x=9x+13

Simple and best practice solution for -96-7x=9x+13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -96-7x=9x+13 equation:


Simplifying
-96 + -7x = 9x + 13

Reorder the terms:
-96 + -7x = 13 + 9x

Solving
-96 + -7x = 13 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
-96 + -7x + -9x = 13 + 9x + -9x

Combine like terms: -7x + -9x = -16x
-96 + -16x = 13 + 9x + -9x

Combine like terms: 9x + -9x = 0
-96 + -16x = 13 + 0
-96 + -16x = 13

Add '96' to each side of the equation.
-96 + 96 + -16x = 13 + 96

Combine like terms: -96 + 96 = 0
0 + -16x = 13 + 96
-16x = 13 + 96

Combine like terms: 13 + 96 = 109
-16x = 109

Divide each side by '-16'.
x = -6.8125

Simplifying
x = -6.8125

See similar equations:

| 3(y-4)=y-6 | | Ay+6=14 | | 6x+3.50=33.20 | | 9-3r=13 | | 6x+1=-92-7x | | 3(2x+1)-5=4(x-3) | | 2t-2y= | | y=x^3+7x^2-245x+35 | | 18=-1.8 | | -52-3=3x+20 | | 2x+15=63-5x | | 6x+5-3x=18+4x | | 1.2=2.5-3b | | 16x^2+16x-1=0 | | 4x^2+6=13 | | C-6=-22 | | x(x+10)+25=0 | | -4(x-5)=12(x+3) | | 6(2x-1)=-11(x+1) | | -2y+3x=2 | | 12x-2y=8 | | 4x+4x=8 | | -9r+5=-28 | | 0.4(y+3)=0.5(y-4) | | 5m+(2m+1)=23 | | 0+50*1-60-60*0+10=10 | | 2+4x=26-x | | 9(m+1)=6m | | 3.49x=78 | | 6x-14=-2x+26 | | x-4=3x-8 | | 3.49+x=78 |

Equations solver categories